1993
DOI: 10.1007/bf00053321
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fracture toughness of a 7XXX aluminum alloy under mode I, mode II and mode III loading

Abstract: A crack in a body can be subjected to three distinct modes of loading: mode I (tensile), mode II (in-plane shear) or mode III (anti-plane shear). In most practical situations, structures are subjected to complex loading and can have flaws or cracks oriented in arbitrary directions. Hence, it is essential to evaluate the fracture toughness of engineering materials under different loading modes to correctly assess their damage tolerance. However, most of the published literature is concerned with only mode I fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1995
1995
1996
1996

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…The mode I1 toughness is therefore less than that of mode I. This is an observation contrary to the observation of Cowie and Tuler [16], Banks-Sills and Sherman [23], and Aoki et al [25], but in agreement with that of Kamat and Eswara Prasad [9] and Mageed and Pandey [45].…”
Section: Stable Crack Growth Analysiscontrasting
confidence: 75%
See 1 more Smart Citation
“…The mode I1 toughness is therefore less than that of mode I. This is an observation contrary to the observation of Cowie and Tuler [16], Banks-Sills and Sherman [23], and Aoki et al [25], but in agreement with that of Kamat and Eswara Prasad [9] and Mageed and Pandey [45].…”
Section: Stable Crack Growth Analysiscontrasting
confidence: 75%
“…However, there has been no study reported in the literature on mode I1 stable crack growth. A number of specimens geometries are designed or considered for measurements of fracture toughness in mode I1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Results based on elastic-plastic fracture mechanics have been presented recently concerning the mode I1 crack growth initiation [21-251.…”
Section: Introductionmentioning
confidence: 99%